Khalifa of Pamir, Custodians of Knowledge - Mikhalev Maxim (Methexis)
This paper explores both social role and spiritual functions of the local religious leaders in Tajikistan sector of Pamir mountains, called Gorno-Badakshan Autonomous Oblast. This remote and isolated mountainous region is criss-crossed by the state borders of China, Pakistan, Afghanistan and Tajikistan and serves as the abode for several obscure ethnic groups that since long have adopted Ismailism, an esoteric branch of Shia Islam. The leader of Ismaili Aga Khan IV helped local people to survive horrors of civil war that ravaged this region in the 1990s, and now effectively administer Gorno-Badakshan Autonomous Oblast through the network oh his local representatives called khalifa. They act as community leaders solving the problems of ordinary villagers of Pamir, yet at the same time they help esoteric Gnostic knowledge of Ismailism to be kept safe in this remotest part of the globe. The paper concludes that this became possible due to innate characteristics of local people, who are not only knowledge-thirsty, but also knowledge-loyal